2012
DOI: 10.1111/j.1708-8208.2012.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Outcomes of Two Implants with Different Prosthetic Interfaces and Neck Configurations: Randomized, Controlled, Split‐Mouth Clinical Trial

Abstract: Both implant designs investigated performed similarly in terms of failure rates, providing successful results up to 1 year after loading. The back-tapered neck configuration with conical connection and built-in platform shifting showed statistically lower marginal bone loss than straight neck configuration with flat-to-flat implant-abutment interface and external-hexagonal connection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
129
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(145 citation statements)
references
References 32 publications
6
129
1
9
Order By: Relevance
“…These findings were confirmed in a recent randomized controlled split-mouth trial, where the use of implants with conical connection and a built-in platform resulted in less crestal bone loss and excellent bone stability over time compared to fixtures with a flat-to-flat external hexagonal connection with abutments of matching diameter [49].…”
Section: Discussionsupporting
confidence: 52%
“…These findings were confirmed in a recent randomized controlled split-mouth trial, where the use of implants with conical connection and a built-in platform resulted in less crestal bone loss and excellent bone stability over time compared to fixtures with a flat-to-flat external hexagonal connection with abutments of matching diameter [49].…”
Section: Discussionsupporting
confidence: 52%
“…This study assessed the effect of splinted crowns and implant length of Morse taper because this connection type exhibits better biomechanical behavior than other connections [17, 18], contributing to bone preservation [19, 20] and lower complications rates [21]. Furthermore, cemented crowns were simulated in this study because they exhibit better biomechanical behavior with Morse taper implants [16] and contribute to greater preservation of the bone tissue, compared with the screwed crown [22].…”
Section: Discussionmentioning
confidence: 99%
“…45 However, in the esthetic zone, it may be prudent to place the implant shoulder 0.5 to 1.0 mm subcrestal 47 so that a proper emergence profile can be achieved. Recent literature also found that subcrestal placement of the microgap 49,50 and the presence of a platform switch 51,52 aid in the preservation of the marginal bone level and, therefore, can be a useful feature in the anterior region where the implant can be placed slightly subcrestal. If the implant is placed too shallow, esthetic complications, such as poor contours of the restoration and visible metal margins, may ensue.…”
Section: Implant Positionmentioning
confidence: 99%